Differences in Pneumococcal and Haemophilus influenzae Natural Antibody Development in Papua New Guinean Children in the First Year of Life - Martinovich, Kelly M.; Rahman, Tasmina; de Gier, Camilla; Seppanen, Elke J.; Orami, Tilda; Granland, Caitlyn M.; Francis, Jacinta; Yoannes, Mition; Corscadden, Karli J.; Ford, Rebecca; Jacoby, Peter; van den Biggelaar, Anita H. J.; et al. (Frontiers in Immunology, 2021)
Background Development of vaccines to prevent disease and death from Streptococcus pneumoniae, and non typeable Haemophilus influenzae (NTHi), the main pathogens that cause otitis media, pneumonia, meningitis and sepsis, are a global priority. Children living in low and lower-middle income settings are at the highest risk of contracting and dying from these diseases. Improved vaccines with broader coverage are required. Data on the natural development of antibodies to putative vaccine antigens, especially in high-risk settings, can inform the rational selection of the best antigens for vaccine development. Methods Serum IgG titres to four pneumococcal proteins (PspA1, PspA2, CbpA, and Ply) and five NTHi antigens (P4, P6, OMP26, rsPilA and ChimV4) were measured in sera collected from 101 Papua New Guinean children at 1, 4, 9, 10, 23 and 24 months of age using multiplexed bead-based immunoassays. Carriage density of S. pneumoniae and H. influenzae were assessed by quantitative PCR on genomic DNA extracted from nasopharyngeal swabs using species-specific primers and probes. All data were log-transformed for analysis using Student’s unpaired t-tests with geometric mean titre (GMT) or density (GMD) calculated with 95% confidence intervals (CI). Results Serum -pneumococcal protein-specific IgG titres followed a “U” shaped pattern, with a decrease in presumably maternal-derived IgG titres between 1 and 4 months of age and returning to similar levels as those measured at 1 month of age by 24 months of age. In contrast, NTHi protein-specific IgG titres steadily increased with age. There was no correlation between antibody titres and carriage density for either pathogen. Conclusion This longitudinal study indicates that the waning of maternal derived antibodies that is usually observed in infants does not occur for NTHi antigens in Papua New Guinean infants. Whether NTHi antigen IgG can be transferred maternally remains to be determined. Vaccines that are designed to specifically increase the presence of protective NTHi antibodies in the first few months of life may be most effective in reducing NTHi disease.